Aktivitas Antibakteri Ekstrak Etanol Bunga Kamboja Merah (Plumeria rubra L.) terhadap Pertumbuhan Bakteri Methicillin-resistant Staphylococcus aureus (MRSA) - Diksha, I Gusti Ngurah Ariestha Satya; Artini, I Gusti Ayu; Trapika, I Gusti Made Gde Surya Chandra; Widhiartini, Ida Ayu Alit (E-Jurnal Medika Udayana, 2024)
Introduction: MRSA is an antibacterial resistance problem that requires serious treatment. The limitations of antibacterials make it difficult to treat infections. The development of alternative antibacterial is needed. Objectives: This study shows the antibacterial effect of ethanol extract of Plumeria rubra L. flowers against MRSA bacteria. Methods: This research is a true experimental research with the only post-test control group design. The Kirby-Bauer test method was used to evaluate the antibacterial activity of ethanol extract of Plumeria rubra L. flowers with concentrations of 20%, 40%, and 60% in triplicate. The test bacteria used MRSA ATCC 33591 bacteria. Antibacterial activity was assessed from the diameter of the inhibition zone formed in bacterial cultures on agar media. Results: The inhibition zone were not formed after ethanolic extract of Plumeria rubra L. flowers at various concentrations. These were not antibacterial activity shown from Plumeria rubra L. flowers extract at concentrations of 20%, 40%, and 60%. Conclusions: The ethanolic extract of Plumeria rubra L. flowers does not show antibacterial activity against MRSA bacteria. Keywords: Red frangipani flowers (Plumeria rubra L.), antibacterial activity, MRSA.